Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00784-020-03456-5
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival microflora in adolescent females with polycystic ovary syndrome and its association with oral hygiene, gingivitis, and selected metabolic and hormonal parameters

Abstract: Objectives Research studies suggest that polycystic ovary syndrome (PCOS) may influence the composition of the oral microflora in women. This study aimed to investigate factors affecting the number of selected periopathogens in a young cohort of females with PCOS and to assess the association between oral hygiene, subgingival microbiome, gingival health, and metabolic and hormonal parameters. Materials and methods Thirty-two subjects with PCOS and twenty-three healthy controls aged 15-19 years were examined pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Homeostasis model assessment-IR (HOMA-IR) was applied using the following formula: HOMA-IR = fasting insulin (μU/mL) × fasting glucose (mmol/L)/22.5 [ 69 , 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Homeostasis model assessment-IR (HOMA-IR) was applied using the following formula: HOMA-IR = fasting insulin (μU/mL) × fasting glucose (mmol/L)/22.5 [ 69 , 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results were compared to the age and sex-specific laboratory reference ranges and the literature data [30,31].…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Recently, it was reported that individuals suffering from PCOS may also experience a higher prevalence and risk of developing periodontal disease ( Machado et al., 2020 ). Subsequently, microbiological changes have been pointed as one of the causes ( Akcalı et al., 2014 ; Lindheim et al., 2016 ; Wendland et al., 2020 ). To date, three studies have investigated changes in oral bacterial species in individuals suffering from PCOS.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…One more study used PCR to evaluate the presence of nine different periodontal bacteria in young individuals with and without PCOS ( Wendland et al., 2020 ). In this study, no particular microbiome alterations could be linked to PCOS.…”
Section: In Vivo Studiesmentioning
confidence: 99%